Religious Print in Settler Australia and Oceania - Stanley, Timothy (Religions, 2021)
A distinctive feature of the study of religion in Australia and Oceania concerns the influence of European culture. While often associated with private interiority, the European concept of religion was deeply reliant upon the materiality of printed publication practices. Prominent historians of religion have called for a more detailed evaluation of the impact of religious book forms, but little research has explored this aspect of the Australian case. Settler publications include their early Bible importation, pocket English language hymns and psalters, and Indigenous language Bible translations. As elsewhere in Europe, Australian settlers relied on print to publicize their understanding of religion in their new context. Recovering this legacy not only enriches the cultural history of Australian settler religion, it can also foster new avenues through which to appreciate Australia’s multireligious and Indigenous heritage.